2016
DOI: 10.1038/ng.3564
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of somatic genome alterations in lung adenocarcinomas and squamous cell carcinomas

Abstract: To compare lung adenocarcinoma (ADC) and lung squamous cell carcinoma (SqCC) and to identify new drivers of lung carcinogenesis, we examined exome sequences and copy number profiles of 660 lung ADC and 484 lung SqCC tumor/normal pairs. Recurrent alterations in lung SqCCs were more similar to other squamous carcinomas than to lung ADCs. Novel significantly mutated genes included PPP3CA, DOT1L, and FTSJD1 in lung ADC, RASA1 in lung SqCC, and KLF5, EP300, and CREBBP in both tumor types. Novel amplification peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
985
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 993 publications
(1,042 citation statements)
references
References 69 publications
49
985
7
1
Order By: Relevance
“…To explore the implication of JAK2 mutations in lung cancers in the context of immunotherapy, we analyzed the TCGA cohort of 515 lung adenocarcinomas with both exome sequencing and RNA-seq data available [5]. While no activating JAK2 mutation is present in the TCGA cohort, JAK2 is amplified in three tumors.…”
Section: Jak2 Pv617f Oncogenic Mutation In 1% Of Nsclcsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the implication of JAK2 mutations in lung cancers in the context of immunotherapy, we analyzed the TCGA cohort of 515 lung adenocarcinomas with both exome sequencing and RNA-seq data available [5]. While no activating JAK2 mutation is present in the TCGA cohort, JAK2 is amplified in three tumors.…”
Section: Jak2 Pv617f Oncogenic Mutation In 1% Of Nsclcsmentioning
confidence: 99%
“…At the molecular pathway level, RTK/RAS/RAF, PI3K-mTOR, and cell cycle pathways are the most frequently altered in lung adenocarcinomas [4]. In addition, the differences of genomic alterations in smokers and nonsmokers have also been investigated [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the IASLC, together with diagnostic companies and pharmaceutical industries, is currently involved in comparing, optimizing and homogenizing different PD-L1 immunohistochemical diagnostic assays. Beside PD-L1 evaluation, other potential predictive tools such as the analysis of tumour nonsynonymous mutation burden 79,80 as well as neo-epitope load 81 , are under investigation. In the near future, additional areas of clinical investigation for immune checkpoint inhibitors will focus on the duration of treatment, as well as on the sequencing of immunotherapy, chemotherapy and targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Since these experiments utilized mouse models with subcutaneous injection of cancer cells, they may not have site-specific features (such as colon-specific or lung-specific) of the tumor immune microenvironment. In addition, a recent large scale comprehensive genomic study reported that the significantly mutated genes in lung adenocarcinomas were most similar to those in glioblastoma and colorectal cancer (19). Therefore, I propose that the roles of PD-1 positive TAMs, and the effects of anti-PD-1/anti-PD-L1 drugs on these TAMs in NSCLC patients are worthy of investigation in future studies, at least in lung adenocarcinoma patients.…”
mentioning
confidence: 99%